2007
DOI: 10.1186/1465-9921-8-50
|View full text |Cite
|
Sign up to set email alerts
|

Peripheral infusion of rat bone marrow derived endothelial progenitor cells leads to homing in acute lung injury

Abstract: Background: Bone marrow-derived progenitors for both epithelial and endothelial cells have been observed in the lung. Besides mature endothelial cells (EC) that compose the adult vasculature, endothelial progenitor cells (EPC) are supposed to be released from the bone marrow into the peripheral blood after stimulation by distinct inflammatory injuries. Homing of ex vivo generated bone marrow-derived EPC into the injured lung has not been investigated so far. We therefore tested the hypothesis whether homing of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
69
1
3

Year Published

2010
2010
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 97 publications
(76 citation statements)
references
References 99 publications
(96 reference statements)
3
69
1
3
Order By: Relevance
“…VEGF induced CD31, VE-cadherin, TF, vWF, and SRF expression. D, cells (11th passage) were seeded on gelatin-coated plates and cocultured for one to three passages with 5 μg/mL AS or AS-Tspan8 exosomes or VEGF: morphology (scale bar: 100 μm) and gene expression (RT-PCR) after one and three passages in comparison with RAEC, BMC, and BMC-derived ECP (31). In cocultures with 5 μg/mL AS-Tspan8 exosomes, ECPs start to form cable-like structures, lose CD133 and VEGFR2, but gain CD31 and VEGFR1 expression, resembling mature ECs.…”
Section: and Cd11bmentioning
confidence: 99%
“…VEGF induced CD31, VE-cadherin, TF, vWF, and SRF expression. D, cells (11th passage) were seeded on gelatin-coated plates and cocultured for one to three passages with 5 μg/mL AS or AS-Tspan8 exosomes or VEGF: morphology (scale bar: 100 μm) and gene expression (RT-PCR) after one and three passages in comparison with RAEC, BMC, and BMC-derived ECP (31). In cocultures with 5 μg/mL AS-Tspan8 exosomes, ECPs start to form cable-like structures, lose CD133 and VEGFR2, but gain CD31 and VEGFR1 expression, resembling mature ECs.…”
Section: and Cd11bmentioning
confidence: 99%
“…In addition to the securely established effects on cancer and immunodeficiency engraftment of bone-marrow-derived cells (BMDC) into lung tissue and cerebellum has been proposed. 7 At the face of Purkinje cell loss and progressive lung destruction several studies have shown that BMDC are able to contribute to neogenesis of cerebellar Purkinje neurons or lung tissue regeneration and protection which is of special interest for a therapeutic approach for A-T. 8,9 In Atm-deficient mice, BMT significantly inhibited tumorigenesis and improved the immunity, weight gain and fitness. 10,11 Our results further showed the migration of CD31 +CD45-endothelial cells and EpCAM+ epithelial cells into the lung tissue of transplanted Atm-deficient mice.…”
Section: Introductionmentioning
confidence: 99%
“…1A). 12 The phenotypes of cultured cells were further characterized according to their ability for uptake of Dil-labeled acetylated-LDL to confirm their endothelial lineage. We incubated the adherent cells with 10 mg/mL Dil-Ac-LDL (Biomedical Technologies, Stoughton, MA) at 378C for 4 h. After the incubation, cells were fixed with 3% formaldehyde for 20 min and viewed under a fluorescent microscope.…”
mentioning
confidence: 99%